An old enemy not to be forgotten during PET CT scanning of cancer patients: tuberculosis - Sümbül, Ahmet Taner; Sezer, Ahmet; Abali, Hüseyin; Gültepe, Bilge; Koçer, Emrah; Reyhan, Mehmet; TonyalI, Önder; Özyilkan, Özgür (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Positron emission tomography–computed tomography (PET CT) scan is commonly used in current medical oncology practice as an imaging method. In this study we present data from cancer patients who were followed at our clinic and suspected of having tuberculosis during PET CT scanning. After the biopsy, they were diagnosed with concomitant tuberculosis. Material and methods : In this study, 14 patients who applied to our clinic and followed up due to cancer, and had PET CT scanning for the preliminary staging or further evaluation, were included. The patients were diagnosed with metastatic or recurrent disease, and their biopsy results revealed tuberculosis. Results : The mean age was 57.8 years with SD (standard deviation) 13.1 years and gender distribution of 78.6% (n = 11) females and 21.4% (n = 3) males. None of the patients had tuberculosis in their personal history (0%). Among the patients, 5 (35.7%) were diagnosed with tuberculosis during the preliminary staging, whereas 9 (64.3%) were diagnosed during the follow-up after the treatment. The median time to tuberculosis diagnosis was 11 months (min–max: 3–24 months) after the treatment. The most commonly involved lymph nodes during PET CT scanning were mediastinal in 8 (64.3%), axillary in 3 (21.4%) and para-aortic in 3 (21.4%) patients. The mean SUV max (maximum standardised uptake value) of lymph node involved by PET CT scanning was defined as 8.5 (SD 2.6). Conclusions : Despite all improvements in modern medicine, tuberculosis is still a serious public health problem. It should always be considered in differential diagnosis while evaluating PET CT scanning results of cancer patients, because it may cause false positive results.